2015
DOI: 10.5755/j01.ms.21.2.7075
|View full text |Cite
|
Sign up to set email alerts
|

Low-weight Impact Behaviour of Carbon Fibre Reinforced Methyl Methacrylate Nanocomposites

Abstract: In this study, the carbon fibre reinforced methyl methacrylate resin composite (CF/MMA) toecaps for safety shoes were manufactured to change impact behaviour by incorporation of nanofillers. Different types of nanofillers such as nanotubes (inorganic halloysite, multiwalled carbon nanotubes) and unmodified and organically modified nanoclays (natural bentonite and montmorillonites) were dispersed inMMA composition. The low-velocity impact test with dropweight machine was performed with respect to the nanofiller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The same author also developed a biodegradable solution of flax fibers and PLA for a toe cap, accomplishing a 50% weigh reduction when compared to their steel counterpart, while sustaining the requirements for quasi-static compressive loading according to ISO 12568 [25]. Zukas et al found a 20% improvement in low velocity impact response, by the addition of nanofillers in carbon fiber reinforced toe caps made of methyl methacrylate resin [26]. More recently, an optimized stacking sequence of E-fiber glass, carbon and aramid fabric layers was suggested by Erden et al [20].…”
Section: Category Of Footwearmentioning
confidence: 99%
“…The same author also developed a biodegradable solution of flax fibers and PLA for a toe cap, accomplishing a 50% weigh reduction when compared to their steel counterpart, while sustaining the requirements for quasi-static compressive loading according to ISO 12568 [25]. Zukas et al found a 20% improvement in low velocity impact response, by the addition of nanofillers in carbon fiber reinforced toe caps made of methyl methacrylate resin [26]. More recently, an optimized stacking sequence of E-fiber glass, carbon and aramid fabric layers was suggested by Erden et al [20].…”
Section: Category Of Footwearmentioning
confidence: 99%
“…As a result, materials science strives to develop polymeric materials that would be characterized by strength properties and lower weight, compared to steel, while ensuring the appropriate functional properties of toecaps. Recent years have seen an increased application of non-metallic materials including composites incorporating polyester, polyamide, and epoxy resins with nanofillers (carbon, aramid, and glass fibers) [10][11][12][13]. Non-metallic materials are highly attractive due to their flexibility of design and additional features, such as electrical insulation, and very importantly, they provide better thermal insulation than metallic toecaps [14].…”
Section: Introductionmentioning
confidence: 99%